IN VITRO ANALYSIS OF ANTIOXIDANT ACTIVITIES OF OXALIS CORNICULATA LINN. FRACTIONS IN VARIOUS SOLVENTS - Ahmed, Dildar; Zara, Saman; Baig, Hira (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
As part of our search for natural antioxidants, this work presents an evaluation of antioxidant activities of methanolic extract of Oxalis corniculata and its sub-fractions in hexane, chloroform, ethyl acetate, n-butanol and water. The total phenolic contents in terms of µg of gallic acid equivalents per mg of dried mass were approximately 21.0, 28.2, 34.5, 162.0, 70.0, and 49.2 in methanolic, hexane, chloroform, ethyl acetate, n-butanolic and aqueous fractions respectively, while the flavonoid contents in these solvents were 362.4, 214.1, 317.1, 177.1, 98.8 and 53.5 respectively in terms of µg of rutin per mg of dried mass. In DPPH assay, the ethyl acetate fraction showed the highest free radical scavenging activity, 24.0% with 1 mg/mL concentration. The second strongest fraction was chloroform (21.5%). The EC50 and TEC50 values of the methanolic extract were 3.63 mg/mL and 23 min respectively. The FRAP values in terms of µg of ascorbic acid equivalents per mg of dried mass for these solvents were 288.0, 1705.3, 437.1, 72.0, 28.0, and 44.0 respectively while total antioxidant activity measured by phosphomolybdate assay in terms of µg of ascorbic acid equivalents per mg of dried mass were 50.0, 117.0, 78.6, 57.8, 3.4 and 8.3 respectively. All the samples showed remarkable ability to inhibit lipid peroxidation exhibiting much better and sustainable peroxidation inhibitory activity than the standard butylated hydroxyanisole